Coping strategies used by migrant women during pregnancy. An integrative review - Herrera Zuleta, Ivett Adriana; Ospina Romero, Angélica María; Esquivel Rubio, Abraham Isaac; Domínguez Chavez, Claudia Jennifer (Investigación y Educación en Enfermería, 2025)
Objective. To analyze the coping strategies for the adaptation of the migrant during pregnancy described in the literature. Methods. Integrative review using the method approached by Whittemore and Knafl. MeSH terms Pregnancy, Migrants and immigrants, and Psychological adaptation, were incorporated in addition to their variants in the databases of Pubmed, Scopus, EBSCO, Science Direct, and Web of Science. Articles that examined the coping strategies used by pregnant migrants to adapt during pregnancy were included. Only the articles published from 2003 to 2023 was considered. After applying the inclusion and exclusion criteria, the articles were analyzed with the CASPe critical reading tool in which quality and consistency were reviewed. Using the software, Atlas.ti, version 23.2.1, content analysis for the categorical construction of data was performed. These strategies were analyzed with the middle-range theory adaptation to life events by Callista Roy. Results. A total of 416 articles were considered. The reviewed articles show 14 coping strategies used by the pregnant migrant, which were grouped into 5 strategies called social support, emotional regulation and transfer, positive attitude strategy, cultural adaptation strategy, and comprehensible language strategy. Conclusion. It was found that the strategy most used by the migrant pregnant woman is social support, followed by positive attitude strategies and comprehensible language; when using these strategies, the results show migrant pregnant women with a decrease in anxiety, fear and a positive attitude towards life and health.